2019
DOI: 10.1177/1049909119847965
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Experiences With Death and Dying Prior to Medical School: A Content Analysis of Students’ Written Reflections

Abstract: Background: Personal experiences with death and dying are common among medical students, but little is known about student attitudes and emotional responses to these experiences. Our objectives were to ascertain matriculating medical students’ experiences with death and dying, describe the range of students’ emotional responses, and identify reactions, behaviors, and perceived roles related to these and future experiences with death. Methods: We provided a writing prompt to newly matriculated medical students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
6
0
4
Order By: Relevance
“…Every doctor, nurse, midwife, and physiotherapist will experience patient death in his work. Most people who choose a medical faculty will encounter such a situation during their studies, which is shown by the tests carried out by future doctors [(20), p. 123-133; (5), p. 110; (6), p. 108; (18), p. 207-228]. These results are consistent with our study, which showed that the vast majority of nursing students meet with the death of the patient very early, and almost all participants of master's studies experienced patient death at least once.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Every doctor, nurse, midwife, and physiotherapist will experience patient death in his work. Most people who choose a medical faculty will encounter such a situation during their studies, which is shown by the tests carried out by future doctors [(20), p. 123-133; (5), p. 110; (6), p. 108; (18), p. 207-228]. These results are consistent with our study, which showed that the vast majority of nursing students meet with the death of the patient very early, and almost all participants of master's studies experienced patient death at least once.…”
Section: Discussionmentioning
confidence: 99%
“…The education process is undoubtedly influenced by students' experience that results from their private lives. It is emphasized that knowing and understanding what future medical practitioners experience before starting education are crucial to correctly choose teaching methods to analyze their own experiences and their use in inpatient care [( 19 ), p. 999–1,007]. Proper preparation of mentors and their positive attitude toward students are the key to establishing an educational relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Las experiencias con la muerte suponen también un importante reto para ayudar a madurar y adaptarse a las tareas propias de la futura profesión, por su carácter motivador para el desarrollo de estrategias de afrontamiento (6) . En las carreras de ciencias de la salud se tiene contacto con la muerte desde el primer año por medio de las clases de disección en anatomía (7)(8)(9) . El proceso de morir y la muerte es un tema difícil de tratar hasta para los profesionales de la salud ya que genera estrés, ansiedad, malestar e incertidumbre.…”
Section: Introductionunclassified
“…6,11 Previous studies evaluated medical student experiences around death and dying or PC through written reflections; however, most of these studies involved isolated clinical PC or hospice experiences and none have studied the narrative reflections of medical students across multiple U.S. medical schools after a dedicated clinical PC elective. [12][13][14][15][16] Our study aimed to understand medical student experiences of a clinical PC elective by analyzing reflective essays from 3 geographically diverse hospital systems in the United States.…”
Section: Introductionmentioning
confidence: 99%